[Ir(tpy)(bpy)Cl] as a Photocatalyst for CO2 Reduction under Visible‐Light Irradiation. Issue 3 (6th October 2017) - Sato, Shunsuke; Morikawa, Takeshi
Abstract: Mononuclear iridium(III) terpyridine (tpy) 2, 2′‐bipyridine (bpy) [Ir(tpy)(bpy)Cl] 2+ photocatalysts (denoted [Ir(bpy)]) were developed for selective CO2 reduction to HCOOH under visible light. The CO2 reduction product could be changed dramatically by substituting a 2‐phenylpyridine (ppy) ligand with bpy, with the mononuclear Ir ppy complex ([Ir(tpy)(ppy)Cl] + ) acting as a photocatalyst for selective CO2 reduction to CO. A mechanistic study showed a structural change in [Ir(bpy)] during the photocatalytic reaction. The [Ir(bpy)] complex was transformed into an iridium–hydride complex ([Ir(tpy)(bpy)H] 2+ ) during an early stage of the photocatalytic reaction. However, [Ir(tpy)(bpy)H] 2+ did not function as a key intermediate in the photochemical CO2 reduction because an additional structural change occurred. The tpy ligand of the Ir complex was reduced to piperidine‐2, 6‐di‐2‐pyridine ligand during the photocatalytic reaction, resulting in the production of [Ir(piperidine‐2, 6‐di‐2‐pyridine)(bpy)H] 2+, which was the actual photocatalyst for HCOOH production. Abstract : Seeing Ir in a new light : Mononuclear iridium(III) complexes [Ir(tpy)(bpy)Cl] 2+ (denoted [Ir(bpy)]; tpy=terpyridine, bpy=2, 2′‐bipyridine) were employed for the selective reduction of CO2 to HCOOH under visible‐light irradiation. Production of HCOOH involved an induction period in which the CO2 reduction product was converted from CO into HCOOH and a small accompanying structural change in [Ir(bpy)] occurred.